Energy Management Improving the Cooling System in a Local Factory - ENG. Moath Abdrabu Eldbari; Muhammad N Radhwi (Budapest International Research and Critics University, 2019)
Development is an ongoing process in all areas and this research studied of a cooling system for a local factory and evaluated to determine the efficiency and capacity of the cooling capacity of the factory at the desired level. ِAfter evaluating the cooling system and studying the case of the local factory, the heat gain loads in the factory was calculated internally and externally and found that there is a deficit in the cooling system by 45% and the suggestion is to improve the cooling system without affecting production or manpower. Accordingly, three points have been developed to improve the cooling system and the first point is reducing the heat gained from lighting by changing fluorescent bulbs by the LED and this step will reduce the heat gain from lighting by 64%. The second point is to reduce the volume space of production zones by installing the ceiling of the gypsum board where the height was reduced from eight to five meters, which reduced the heat gained by 37% from the walls. The third point is the installation of better insulation materials and has been proposed rock wool material for the roof and the material Rigid expanded board for walls and these materials have reduced 85% of the heat gain from the roof and 20% of the walls. The total rate of improvement in the cooling system completely (internal and external heat gain) is 25% or in other words, can be through the implementation of these points reduce cooling load by 25%.